1990
DOI: 10.2337/diacare.13.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Area Under the Curve: Methodological Aspects

Abstract: To specify the influence of methods used in estimating area under the curve (AUC) and the meaning of total and incremental AUC, 75 glycemic responses to a mixed meal were studied in 75 diabetic patients, 39 with insulin-dependent diabetes mellitus and 36 with non-insulin-dependent diabetes mellitus. AUC was integrated with five computerized methods: polynomial interpolation of third and fourth degree, trapezoidal rule, Simpson's integration, and cubic interpolatory splines. Although these methods gave signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
179
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(186 citation statements)
references
References 0 publications
1
179
0
3
Order By: Relevance
“…Post hoc comparisons (Tukey's test) were performed to pinpoint specific differences in significant interaction means. The AUC and the incremental AUC (iAUC) was calculated for hormones and substrates at the clamped initial euglycaemia (0-30 min), hypoglycaemia (90-130 min), post-hypoglycaemic euglycaemia (150-190 min) and hyperglycaemia (210-250 min) according to the trapezoidal rule (with subtraction of the basal values for iAUC) [19] and analysed by paired or unpaired Student's t-test as appropriate. Data in the text are given as mean±SE and were considered to be significantly different at p<0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Post hoc comparisons (Tukey's test) were performed to pinpoint specific differences in significant interaction means. The AUC and the incremental AUC (iAUC) was calculated for hormones and substrates at the clamped initial euglycaemia (0-30 min), hypoglycaemia (90-130 min), post-hypoglycaemic euglycaemia (150-190 min) and hyperglycaemia (210-250 min) according to the trapezoidal rule (with subtraction of the basal values for iAUC) [19] and analysed by paired or unpaired Student's t-test as appropriate. Data in the text are given as mean±SE and were considered to be significantly different at p<0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Both of these metabolic alterations contribute to the complications of diabetes. Therefore, fluctuations in blood glucose levels should be taken into consideration while assessing the risk of late complications of diabetes (14,24). In the present study, we observed postprandial glucose fluctuations in both groups, using GLU and ASP, although without any statistical difference in variation in glucose levels.…”
Section: :4mentioning
confidence: 43%
“…A commercially available radioimmunoassay kit was used to assess glucagon (EMD Millipore, Darmstadt, Germany) (Clevenger, Parker Jones, Tanaka, Seals, & DeSouza, 2002). The net incremental area under the curve (iAUC) for plasma glucose and insulin was calculated using the trapezoidal method (Clevenger et al., 2002) as it was shown to be more strongly correlated with glycemic rise than total AUC (Le Floch, Escuyer, Baudin, Baudon, & Perlemuter, 1990). …”
Section: Methodsmentioning
confidence: 99%